1992
DOI: 10.1002/j.2333-8504.1992.tb01474.x
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Characteristics Related to Irt Parameter Invariance With the Test of English as a Foreign Language

Abstract: IRT equating methods have been used successfully with the TOEFL® test for many years, and for the most part the observed properties of items have been consistent with model predictions. However, items that do not appear to hold their IRT pretest estimates do exist. If relationships can be found between features of TOEFL items in pretest calibrations and subsequent lack of model‐data fit when these items are used in final forms, steps to eliminate the use of such items in TOEFL final forms can be taken. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Wise, Chia, and Park (1989) found that item order and other item context alterations impacted low-achieving test-takers more than high-achieving test-takers on tests of work knowledge and arithmetic reasoning. In addition, Way, Carey, and Golub-Smith (1992) found that TOEFL reading comprehension items that were pretested toward the beginning of the section but that appeared toward the end of the section on the operational test became more difficult, but items pretested near the end of the section and operationally tested near the beginning of the section became easier. These studies suggest that item position effects can vary depending on factors such as how much the item position changes, the direction of change (i.e., toward the beginning of the test versus toward the end of the test), and the ability levels of the test-takers.…”
Section: Related Literaturementioning
confidence: 96%
“…Wise, Chia, and Park (1989) found that item order and other item context alterations impacted low-achieving test-takers more than high-achieving test-takers on tests of work knowledge and arithmetic reasoning. In addition, Way, Carey, and Golub-Smith (1992) found that TOEFL reading comprehension items that were pretested toward the beginning of the section but that appeared toward the end of the section on the operational test became more difficult, but items pretested near the end of the section and operationally tested near the beginning of the section became easier. These studies suggest that item position effects can vary depending on factors such as how much the item position changes, the direction of change (i.e., toward the beginning of the test versus toward the end of the test), and the ability levels of the test-takers.…”
Section: Related Literaturementioning
confidence: 96%
“…Design features such as construct specification, content coverage, item format, item representations, fairness, and nature of scoring criteria are discussed by Gitomer (1997), Lane (1993), and Linn, Baker, & Dunbar (1991) for example. Research in educational measurement journals describes studies that examine how well an item "fits" the psychometric model used to scale the student responses (e.g., Tang, 1994;Thissen & Steinberg, 1988;Way, Carey, and Golub-Smith, 1992). An item that fits the model is considered to be a well-functioning item for which the observed student performance matches the expected performance based on the model used.…”
Section: Mathematics Published Curriculum and Evaluation Standards Fomentioning
confidence: 99%
“…Divgi (1986) documented changes in item parameter estimates in an early application of the Armed Services Vocational Aptitude Battery (CAT-ASVAB). Several researchers have investigated causes of item parameter drift in testing programs that utilized IRT in test construction and equating over time (Eignor & Stocking, 1986;Kolen & Harris, 1990;Sykes & Fitzpatrick, 1992;Way, Carey, & Golub-Smith, 1992).…”
mentioning
confidence: 99%